Ireland and Shadow Banking (Non Bank Financial Intermediaries): A critical analysis of the Section 110 tax regime - Doyle, Cillian (Trinity College Dublin. School of Business. Discipline of Business & Administrative Studies, 2026)
Ireland’s tax driven industrial policy rests on two pillars. Attracting and fostering FDI and encouraging activities within the International Financial Services Centre (IFSC). This thesis concerns the latter. It focuses on an important but controversial tax incentive – Section 110 (TCA 1997) – applicable to a subset of Irish Special Purpose Vehicles (SPVs). These SPVs are engaged in shadow banking activities and are generally established by foreign sponsors. Section 110 was introduced in 1997 to promote the IFSC as a hub for securitisation SPVs, but it has been expanded to encompass a broader range of financing activities and asset classes. Although firms are nominally subject to the 25% tax rate on passive income, they are in effect ‘tax neutral’. This outcome arises primarily from the tax deductibility of interest on their issued financial instruments, a feature described as ‘unique’ within Irish tax legislation. Within a corporate group structure, these firms are highly attractive because profits generated from underlying assets can be efficiently extracted as deductible interest payments. This minimises taxable income to near zero whist maintaining control over cash flows. In addition, outbound interest payments made by firms are frequently not taxed in the recipient jurisdiction, giving rise to situations of ‘double non-taxation’. As a result, the regime incentivises high levels of debt issuance and creates opportunities for aggressive tax planning and profit shifting, leading to base erosion for other jurisdictions. The scale of the tax benefit is directly linked to the volume of debt issued, with the primary constraint being the firm’s pre-interest cost profitability. This thesis is motivated by two principal concerns. Firstly, the growth of shadow banking activities heightens systemic risks, with the expansion of Ireland’s sector posing possible threats to financial stability. Secondly, aggressive tax practices associated with the regime have attracted scrutiny at the EU level, particularly in the context of compliance with measures such as the Anti-Tax Avoidance Directive (ATAD) and interest limitation rule (ILR). Section 110 has attracted little academic research either in terms of its upside benefits and/or downside risks. This is likely attributable to the absence of any publicly available dataset of qualifying firms. Nevertheless, policymakers describe it as ‘very successful’. Industry sources state that it has made Ireland the global ‘jurisdiction of choice’ for SPVs. This thesis adopts an empirical approach to critically evaluating the regime. Its central objective is to assess whether the substantial fiscal cost of this tax expenditure is justified by its relatively narrow and concentrated domestic benefits, primarily professional service fees accruing to a small number of firms. These benefits are weighed against a range of potential risks, including financial instability, regulatory challenges, revenue losses (both domestically and internationally), and any associated reputational damage arising from this. To address this question, the thesis constructs a novel dataset capturing the population of firms over the period 1997 to 2020. Three important subpopulations were then identified from this with corresponding datasets constructed from statutory filings, including financial statements, annual returns, and prospectuses submitted to the Company Registration Office (CRO). This allowed for an interdisciplinary undertaking of various financial/tax, economic and legal analyses. The three subpopulations analysed as part of this thesis are as follows; • Section 110 firms used for the purposes of securitisation (Chapter 3). • Section 110 firms used nominally for credit provision for Russian MNEs/state owned enterprises (Chapter 4). • Section 110 firms used by Ireland’s aircraft leasing sector (Chapter 5). Financial risks posed by the regime were identified via banks and aircraft lessors which encountered difficulties during the Great Financial Crash, the Russian Financial Crisis (2014-16) and Covid19 pandemic. Reputational/regulatory risks were identified via potential illicit financial flows to Russian MNEs and other governance issues. Revenue risks posed to other countries are highlighted throughout. Overall, the analysis of this thesis suggests the regime delivers limited direct economic benefits to Ireland in terms of employment or tax revenue. Instead, its primary domestic gains accrue to a relatively small group of influential Dublin based professional service firms.
APPROVED
Keywords: Shadow banking; SPVs; financial and regulatory risk; tax avoidance